2020
DOI: 10.1155/2020/8845649
|View full text |Cite
|
Sign up to set email alerts
|

Trefoil System for the Treatment of Mandibular Edentulism: A Case Report with 30 Months Follow-Up

Abstract: The purpose of this work is to describe a clinical case of full-arch mandible rehabilitation with a fixed prosthesis on three implants. The chosen protocol is the Trefoil system by Nobel (Nobel Biocare, Zurich, Switzerland) that allows to realize a mandibular fixed rehabilitation on three particularly designed fixtures through the use of prefabricated surgical guides and a preassembled bar on which the prosthesis is built. Both surgical and prosthetic procedures were completed without complications, and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, the surgical protocol is not as simple as it sounds and the clinician must be well trained to manage any intraoperative complications. 14 Considering the results presented in the study, the lowest stresses in cortical and trabecular bone were observed in the trefoil model. The low stress generation in both canine and molar regions indicates that this system will bring successful results when used with the right indication and appropriate surgical technique.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…On the other hand, the surgical protocol is not as simple as it sounds and the clinician must be well trained to manage any intraoperative complications. 14 Considering the results presented in the study, the lowest stresses in cortical and trabecular bone were observed in the trefoil model. The low stress generation in both canine and molar regions indicates that this system will bring successful results when used with the right indication and appropriate surgical technique.…”
Section: Discussionmentioning
confidence: 75%
“…18 For this reason, the Treofil system was defined with the promise of fewer implants and faster treatment. 14 This method, which is also interesting in terms of patient compliance, was included in our study to investigate the reliability of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This area has been used in severe bone atrophy, in oncological resections or after regenerative procedures in blocks. Currently there are various bone anchoring options such as the use of zygomatic mandibular implants, trefoil technique (Trefoil™) and bicortical implants (Strategic Implant®) that have offered adequate and salvage results in full arch rehabilitation treatment [27][28][29].…”
Section: Therapeutic Options: Bone Grafting Versus Buttress Implant Conceptmentioning
confidence: 99%
“…This system consists of three straight implants, a prefabricated compensation bar and various components such as a round abutment , two framework discs , a screw disc and a clinical screw. [ 6 11 ] The prefabricated bar has adaptive joints which aid in the compensation of vertical, horizontal, and angular misfit.…”
Section: Introductionmentioning
confidence: 99%